Baltic and Icelandic Experiences of Capital Flows and Capital Flow Measures - Groenn, Audun (IMF Working Papers; Working Paper, 2013)
The aim of this empirical study is to describe and provide analysis on the experience of managing capital flows in Iceland and the Baltic countries. During the build-up of the crisis, there were shortcomings in macroeconomic policies and in the policy mix, as well as in financial supervision in the countries covered. While the use of traditional macroeconomic and structural policies was far from exhausted, recognizing that there are no substitutes for sound macroeconomic policies, with an IMF framework on capital flows in place prior to the crisis, it might have been easier for the IMF and national policymakers to identify accelerating problems at an early stage and address them with targeted measures.